Past, Present and Future Developments in New Zealand's Terms of Trade - Philip Borkin (New Zealand Government, The Treasury, 2006)
This paper looks at the importance of the terms of trade for the New Zealand economy by examining the impact of changes in the trend and volatility of the terms of trade on economic growth. It is found that the volatility in the terms of trade has had a negative impact on New Zealand's economic growth between 1950 and 2005. However, it is found that rather than the level of the terms of trade having an impact on growth, it is the level of export prices that have had a significant positive effect with the level of import prices having an insignificant impact. This paper also examines the historical patterns in the trend and volatility to see if and why they have changed over time. As New Zealand is largely an exporter of primary commodities and importer of manufactures, the Prebisch- Singer hypothesis suggests that its terms of trade should have declined over time. However, this paper finds that the terms of trade has not declined and in fact, is showing an increasing trend since 1974. It is also found that the volatility in the terms of trade has declined over time. Using this evidence as well as other issues such as world trade reform and China, this paper draws conclusions as to future movements of New Zealand's terms of trade as well as any possible economic growth implications.
Keywords: E30; F10; F41; F43; 330; Terms of trade; Commodity Prices; New Zealand; Economic Growth; Prebisch-Singer Hypothesis